Photo-initiated self-suspending proppant as well as preparation method and application thereof
Through photoinitiation technology, the modified polyacrylamide is constructed on the surface of quartz sand, which solves the problems of high cost and complex process of quartz sand proppant modification in the prior art, and achieves efficient modification and low-cost preparation, which improves the suspension performance and oil and gas mining effect of quartz sand.
Patent Information
- Application Number
- CN202411744020.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-30
- Publication Date
- 2025-03-07
AI Technical Summary
In the prior art, the surface modification of quartz sand proppants requires pre-construction of chemical bonds, resulting in high production costs and complex processes.
The modified polyacrylamide is constructed on the surface of quartz sand by photoinitiation technology, and polymerization is carried out under ultraviolet light irradiation by acrylamide, ethylene monomer, sulfonic acid monomer, crosslinking agent and photoinitiator, and directly adhered to the surface of quartz sand.
The efficient modification of quartz sand proppant is achieved, which reduces the preparation cost and process complexity, while maintaining the expansion performance of traditional heat-induced methods, improving the suspension performance of quartz sand and the oil and gas mining effect.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of oil and gas field fracturing proppants, and relates to a light-triggered self-suspending proppant and a preparation method and application thereof. Background Art
[0002] Fracturing technology is one of the important technologies for increasing the single well production and recovery rate of unconventional oil and gas reservoirs. Its core is that the fracturing fluid carries the proppant into the formation and fractures the formation to form a fracture network with sufficient length, sufficient width and certain conductivity, thereby providing a seepage channel for oil and gas extraction. In this technology, proppant has always been the key to the fracturing transformation effect and fracturing success rate. At present, quartz sand, ceramsite and coated proppant are still the three commonly used proppants in fracturing technology. Due to its advantages of low cost, high hardness, strong wear resistance and strong chemical stability, quartz sand is currently the most widely used fracturing proppant.
[0003] In recent years, the difficulty of exploration and development of unconventional natural oil and gas resources has increased significantly, while the demand for oil and gas production has increased significantly. This puts higher requirements on the performance of quartz sand proppants in fracturing technology. At the same time, quartz sand proppants have problems such as easy sedimentation and inability to reach the farther end of the rock fracture. Therefore, the surface modification of quartz sand proppants has become a hot topic in oil and gas field exploitation research. In recent years, a self-suspending proppant is a layer of water-absorbent polymer coated on the surface of quartz sand, which is allowed to absorb water and swell in the fracturing fluid to reduce its sedimentation rate and enable the quartz sand to move to the farther end of the fracture. However, the current modification method is mainly thermally induced, which has high energy consumption, and most thermally induced self-suspending proppants are prepared by first chemically modifying the surface, and then compounding the modifier with the substrate by using the reaction between chemical bonds. The pre-chemical modification on the surface of quartz sand increases the preparation cost of the self-suspending proppant. Summary of the invention
[0004] In view of the problems existing in the prior art, the present invention provides a light-triggered self-suspending proppant and a preparation method and application thereof, thereby solving the technical problem that the surface of the modified quartz sand proppant prepared by the prior art method needs to be pre-constructed with chemical bonds and then subjected to composite modification, and at the same time solving the problems of high cost and complicated preparation process in the preparation of surface-modified quartz sand proppant by the prior art method.
[0005] The present invention is achieved through the following technical solutions: A method for preparing a light-triggered self-suspending proppant comprises the following steps: S1: acrylamide, vinyl monomer, sulfonic acid monomer, crosslinking agent and photoinitiator are dissolved in water by stirring, and the pH value of the system is adjusted to 3-7 to prepare a modified solution; S2: adding quartz sand into the modified liquid to carry out a light-initiated reaction to obtain the suspended proppant.
[0006] Preferably, in step S1, the mass ratio of acrylamide, vinyl monomer, sulfonic acid monomer and cross-linking agent is (0.2-1):(0.1-0.9):(0.07-0.15):(0.005-0.025).
[0007] Preferably, in step S1, the amount of the photoinitiator used is 0.05% to 0.25% of the mass of the modified liquid.
[0008] Preferably, in step S1, sodium hydroxide, potassium hydroxide and sodium bicarbonate are used to adjust the pH value of the system.
[0009] Preferably, in step S2, the quartz sand is pretreated before being added to the modified liquid; the pretreatment is to place the quartz sand in a mixed solution of water and ethanol, stir and wash it, and then dry it.
[0010] Preferably, the ratio of the quartz sand to the mixed solution of water and ethanol is (4-12) g: (50-90) mL. Preferably, during the photo-initiated reaction, the wavelength of the light source used is one of 254 nm, 312 nm and 365 nm, and the photo-initiated reaction time is 4 to 8 h.
[0011] Preferably, after the light-initiated reaction, the obtained product is dried, and the dried product is ground to 40-70 meshes to obtain the suspension proppant. A light-triggered self-suspending proppant is prepared by the above method; the expansion rate of the self-suspending proppant is 3.0-5.0.
[0012] The above-mentioned light-triggered self-suspending proppant is used in oil and gas production.
[0013] Compared with the prior art, the present invention has the following beneficial technical effects: The invention discloses a method for preparing a photo-triggered self-suspending proppant. Modified polyacrylamide is constructed on the surface of quartz sand by photo-triggered method. In the modification process, acrylamide, ethylene monomer, sulfonic acid monomer, cross-linking agent and photo-triggered agent are used to generate modified polyacrylamide on the surface of quartz sand. In the polymerization process, each monomer is gradually polymerized under the irradiation of ultraviolet light and attached to the surface of quartz sand. No chemical reagent is required to construct functional groups on the surface of quartz sand in advance. The modified polyacrylamide is bonded to the surface of quartz sand by its viscosity. Compared with the traditional heat-triggered self-suspending proppant, the reaction method is simpler, the use amount of chemical reagent is reduced, and the expansion performance of the photo-triggered modified self-suspending proppant is not reduced compared with the heat-triggered one, thereby saving the time and cost of preparing the self-suspending proppant. The modified polyacrylamide contains hydrophilic groups (such as amide groups, carboxyl groups, etc.) on the molecular chain. These groups can form hydrogen bonds with water molecules, thereby enhancing the polymer's ability to adsorb water. At the same time, the polymer network structure formed by light-induced polymerization has a large specific surface area and porosity, which can accommodate more water molecules and improve water absorption performance. After the modified polyacrylamide on the surface of quartz sand absorbs water and swells, the quartz sand is effectively self-suspended in water, realizing a self-supporting process. The modification method in the present invention is simple, the design is reasonable, and the prepared quartz sand proppant has excellent suspension performance, which can effectively reduce the cost of oil and gas production, increase oil and gas production, and meet the requirements of unconventional oil and gas reservoir production.
[0014] Furthermore, in step S1, the mass ratio of acrylamide, ethylene monomer, sulfonic acid monomer and cross-linking agent is (0.2-1):(0.1-0.9):(0.07-0.15):(0.005-0.025), which effectively controls the degree of polymerization of the polymer, controls the swelling process of the polymer, and realizes the rapid swelling of the self-supporting agent.
[0015] Furthermore, in step S1, the amount of the photoinitiator is 0.05% to 0.25% of the mass of the modified liquid. The photoinitiator can quickly generate active free radicals under ultraviolet light irradiation, thereby initiating a polymerization reaction. An appropriate amount of photoinitiator can ensure that the polymerization reaction reaches a higher conversion rate in a shorter time, thereby improving the polymerization efficiency. The amount of the photoinitiator directly affects the rate and degree of polymerization of the polymerization reaction. An appropriate amount of photoinitiator can enable the polymerization reaction to proceed under suitable conditions, thereby controlling the molecular weight distribution and degree of polymerization of the polymerization product, and obtaining a polyacrylamide product with excellent performance.
[0016] Further, in step S2, before adding quartz sand to the modified solution, the quartz sand is pretreated; the pretreatment is to place the quartz sand in a mixed solution of water and ethanol, stir and clean it, and then dry it. The mixed solution of water and ethanol has good solubility and cleaning ability, and can effectively remove impurities such as soil, grease, and organic matter on the surface of the quartz sand, thereby improving the purity of the quartz sand. By cleaning, the contamination of the modified solution by quartz sand in subsequent polymerization reactions can be reduced, and the smooth progress of the polymerization reaction and the quality of the product can be ensured. The surface of the quartz sand after cleaning is cleaner, which is conducive to the growth and fixation of polymer chains on its surface. After adding the modified solution, the pretreated quartz sand can better react with the polymer chain and improve the polymerization efficiency.
[0017] Furthermore, the ratio of the quartz sand to the mixed solution of water and ethanol is (4-12) g: (50-90) mL. The mixed solution of water and ethanol can form a certain surface tension, which helps to wash away the tiny particles and pollutants on the surface of the quartz sand. At the same time, the volatility of ethanol can also help to take away some pollutants, thereby improving the cleaning effect. The surface of the quartz sand after cleaning is purer, which is conducive to the polymer to adhere more firmly to the surface of the quartz sand.
[0018] Furthermore, after the light-initiated reaction, the obtained product is dried and ground to 40-70 meshes to obtain the suspended proppant. The grinding process separates the self-suspending proppant that is solidified by the viscosity of the modified polyacrylamide, so that a certain amount of modified polyacrylamide is attached to the surface of each quartz sand, thereby obtaining a self-suspending proppant. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0020] Figure 1 Figure 1 is a SEM image of the quartz sand proppant before and after modification. Figure (a) is a SEM image of the original quartz sand proppant, and Figure (b) is a SEM image of the light-triggered self-suspending proppant prepared in Example 4.
[0021] Figure 2 The ultra-depth-of-field microscope images of the quartz sand proppant before and after modification. Among them, Figure (a) is an ultra-depth-of-field microscope image of the original quartz sand proppant, Figure (b) is an ultra-depth-of-field microscope image of the photo-induced self-suspending proppant prepared in Example 4, and Figure (c) is an ultra-depth-of-field microscope image of the photo-induced self-suspending proppant prepared in Example 4 after hydration.
[0022] Figure 3 Fourier transform infrared spectra of quartz sand proppant before and after modification.
[0023] Figure 4 Figure 2 is a diagram showing the suspension effect of quartz sand proppants before and after modification; Figure (a) is a diagram showing the suspension effect of the original quartz sand proppants, and Figure (b) is a diagram showing the suspension effect of the light-induced self-suspended proppants. DETAILED DESCRIPTION
[0024] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0025] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0026] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values within the range (including integers and fractions).
[0027] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”
[0028] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0029] The present invention provides a light-triggered self-suspending proppant and a preparation method thereof, comprising the following steps: S1: adding quartz sand to a mixed solution of water and ethanol, stirring and washing at 40-80°C for 1-5 h, and then drying at 80°C for 6 h to obtain pretreated quartz sand; The ratio of quartz sand to the mixed solution of water and ethanol is (4-12) g: (50-90) mL; the mass ratio of water to ethanol in the mixed solution is 7:3; S2: adding acrylamide, vinyl monomer, sulfonic acid monomer, crosslinking agent and photoinitiator into water, stirring to fully dissolve them, and then using a pH adjuster to adjust the pH value of the solution to 3-7 to obtain a modified solution; Wherein, the vinyl monomer is one of acrylic acid, 3-phenylacrylic acid, cis-butenedioic acid, cis-octadec-9-enoic acid and hexadienoic acid; The sulfonic acid monomer is one of 2-acrylamide-2-methylpropanesulfonic acid, 2-acrylamide dodecanesulfonic acid, sodium vinyl sulfonate, sodium allyl sulfonate and sodium p-styrene sulfonate; The cross-linking agent is one of N,N-methylenebisacrylamide and tetraallylammonium chloride; The photoinitiator is one of 2-hydroxy-1-(4-(2-hydroxy-2-methylpropionylphenyl)benzyl)-2-methyl-1-propanone, 2,4,6(trimethylbenzoyl)diphenylphosphine oxide, 2-phenylbenzyl-2-dimethylamine-1-(4-morpholinobenzylphenyl)butanone, 2-hydroxy-2-methyl-1-phenyl-1-propanone and 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone.
[0030] The mass ratio of acrylamide, vinyl monomer, sulfonic acid monomer and cross-linking agent is (0.2~1):(0.1~0.9):(0.07~0.15):(0.005~0.025).
[0031] The amount of the photoinitiator used accounts for 0.05% to 0.25% of the mass of the modified liquid.
[0032] The pH adjusters are sodium hydroxide, potassium hydroxide and sodium bicarbonate.
[0033] S3: After adding the pretreated quartz sand in step S1 to the modified liquid in step S2, the pretreated quartz sand is moved to an ultraviolet light initiation device, and a photoinitiation reaction is carried out using ultraviolet light with a wavelength of 254 nm, 312 nm or 365 nm. After reacting for 4 to 8 hours, the product is dried at 50 to 90° C. for 6 to 10 hours, and the dried product is ground into 40 to 70 meshes to obtain the self-suspending proppant.
[0034] The expansion rate of the self-suspending proppant prepared by the invention is 3.0-5.0.
[0035] The quartz sand proppant prepared by the present invention has excellent suspension performance, can effectively reduce the cost of oil and gas production, increase oil and gas production, meet the requirements of unconventional oil and gas reservoir production, and has broad application prospects in unconventional oil and gas production.
[0036] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0037] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.
[0038] Example 1 (1) Add 4.0 g of quartz sand to a mixed solution of 35 mL of deionized water and 15 mL of ethanol, place it on a magnetic stirrer and stir it at 40 °C for 1 h, then dry it in an oven at 80 °C for 6 h.
[0039] (2) Add 0.2 g acrylamide, 0.1 g 3-phenylacrylic acid, 0.07 g 2-acrylamidododecanesulfonic acid, 0.005 g tetraallylammonium chloride and 0.05% 2-hydroxy-1-(4-(2-hydroxy-2-methylpropionylphenyl)benzyl)-2-methyl-1-propanone into a beaker, add deionized water to make the total monomer mass fraction 10%, stir until mixed evenly, and adjust the pH to 3 with sodium hydroxide.
[0040] (3) Add 4 g of the pretreated quartz sand in step (1) to the mixed solution in step (2), move to a photoinitiator and initiate with 254 nm ultraviolet light for 4 h, dry in an oven at 50 °C for 6 h, and grind to obtain a self-suspending proppant.
[0041] Example 2 (1) Add 6.0 g of quartz sand to a mixed solution of 42 mL of deionized water and 18 mL of ethanol, place it on a magnetic stirrer and stir it at 50 °C for 2 h, then dry it in an oven at 80 °C for 6 h.
[0042] (2) Add 0.4 g acrylamide, 0.3 g cis-butenedioic acid, 0.09 g sodium vinyl sulfonate, 0.010 g N,N-methylenebisacrylamide and 0.10% 2,4,6 (trimethylbenzoyl) diphenylphosphine oxide into a beaker, add deionized water to make the total monomer mass fraction 15%, stir until the mixture is uniform, and adjust the pH to 4 with potassium hydroxide.
[0043] (3) Add 6 g of the pretreated quartz sand in step (1) to the mixed solution in step (2), move to a photoinitiator and initiate with 365 nm ultraviolet light for 5 h, dry in an oven at 60 °C for 7 h, and grind to obtain a self-suspending proppant.
[0044] Example 3 (1) Add 8.0 g of quartz sand to a mixed solution of 49 mL of deionized water and 21 mL of ethanol, place it on a magnetic stirrer and stir it at 60 °C for 3 h, then dry it in an oven at 80 °C for 6 h.
[0045] (2) Add 0.6 g acrylamide, 0.5 g cis-octadec-9-enoic acid, 0.11 g sodium allyl sulfonate, 0.015 g tetraallylammonium chloride and 0.15% 2-phenylbenzyl-2-dimethylamine-1-(4-morpholinobenzylphenyl)butanone into a beaker and add deionized water to make the total monomer mass fraction reach 20%. Stir until the mixture is uniform and adjust the pH value to 5 with sodium bicarbonate.
[0046] (3) Add 8 g of the pretreated quartz sand in step (1) to the mixed solution in step (2), move to a photoinitiator and initiate with 312 nm ultraviolet light for 6 h, dry in an oven at 70 °C for 8 h, and grind to obtain a self-suspending proppant.
[0047] Example 4 (1) Add 10.0 g of quartz sand to a mixed solution of 56 mL of deionized water and 24 mL of ethanol, place it on a magnetic stirrer and stir it at 70 °C for 4 h, then dry it in an oven at 80 °C for 6 h.
[0048] (2) Add 0.8 g acrylamide, 0.7 g acrylic acid, 0.13 g 2-acrylamide-2-methylpropanesulfonic acid, 0.020 g N,N-methylenebisacrylamide and 0.20% 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone into a beaker, add deionized water to make the total monomer mass fraction 25%, stir until the mixture is uniform, and adjust the pH to 6 with sodium hydroxide.
[0049] (3) Add 10 g of the pretreated quartz sand in step (1) to the mixed solution in step (2), move to a photoinitiator and initiate with 254 nm ultraviolet light for 7 h, dry in an oven at 80 °C for 9 h, and grind to obtain a self-suspending proppant.
[0050] Example 5 (1) Add 12.0 g of quartz sand to a mixed solution of 63 mL of deionized water and 27 mL of ethanol, place it on a magnetic stirrer and stir it at 80 °C for 5 h, then dry it in an oven at 80 °C for 6 h.
[0051] (2) Add 1.0 g acrylamide, 0.9 g hexadecene, 0.15 g sodium p-styrene sulfonate, 0.025 g tetraallylammonium chloride and 0.25% 2-hydroxy-2-methyl-1-phenyl-1-propanone into a beaker, add deionized water to make the total monomer mass fraction 30%, stir until the mixture is uniform, and adjust the pH to 7 with sodium hydroxide.
[0052] (3) Add 12 g of the pretreated quartz sand in step (1) to the mixed solution in step (2), move to a photoinitiator and initiate with 254 nm ultraviolet light for 8 h, dry in an oven at 90 °C for 10 h, and grind to obtain a self-suspending proppant.
[0053] The light-triggered self-suspending proppants prepared in Examples 1 to 5 all have good suspension performance, and the light-triggered self-suspending proppant prepared in Example 4 is used as an example for description below.
[0054] Figure 1 The following are SEM images of quartz sand proppants before and after modification. Figure (a) is the SEM image of the original quartz sand proppants, and Figure (b) is the SEM image of the photo-initiated self-suspended proppants. Figure (a) shows that the surface of the original quartz sand is smooth and flat. Figure (b) shows that the surface of the modified quartz sand proppants is adhered to the modified polyacrylamide that is photo-initiated and polymerized.
[0055] Figure 2 The following are ultra-depth microscopic images of quartz sand proppants before and after modification. Among them, Figure (a) is an ultra-depth microscopic image of the original quartz sand proppants, Figure (b) is an ultra-depth microscopic image of the photo-induced self-suspending proppants, and Figure (c) is an ultra-depth microscopic image of the photo-induced self-suspending proppants after hydration. Figure (a) shows that the surface of the original quartz sand is smooth and flat, and is not combined with other substances. Figure (b) shows that white modified polyacrylamide is adhered to the surface of the photo-induced self-suspending proppants. Figure (c) shows that after the photo-induced self-suspending proppants absorb water, the adhered modified polyacrylamide absorbs water and expands, thereby slowing down the sedimentation of the quartz sand proppants in water.
[0056] Figure 3 FT-IR of quartz sand proppant before and after modification. As shown in the figure, 3420 cm -1 The left and right sides are the characteristic absorption peaks of free -NH2, 3204 cm -1 The left and right sides are the characteristic absorption peaks of associated -NH2, 2930 cm -1The left and right sides are the characteristic absorption peaks of methylene antisymmetric stretching vibration, 1675 cm -1 The left and right sides are the characteristic absorption peaks of carbonyl, corresponding to the stretching vibration of amide C=O, 1551cm -1 The left and right sides are secondary amide NH bending vibrations, 1108 cm -1 The absorption peaks on the left and right are related to the stretching vibration of CN, and the absorption peak of -CH is at 1431 cm -1 About 1047 cm -1 Then it is -SO3 -1 Symmetrical and asymmetric stretching vibration absorption peaks. 1047 cm -1 、779cm -1 、681 cm -1 and 468 cm -1 The peaks on the left and right are the symmetrical stretching vibration peaks of Si-O bonds, indicating that the modified polyacrylamide is successfully bonded to the surface of the quartz sand proppant.
[0057] Figure 4 Figure 1 shows the suspension effect of quartz sand proppants before and after modification, where Figure (a) shows the suspension effect of the original quartz sand proppants, and Figure (b) shows the suspension effect of the light-induced self-suspended proppants. As can be seen from Figure (a), the original quartz sand proppants quickly settle in the water and cannot remain suspended for a long time, resulting in a short migration distance in the rock cracks. As can be seen from Figure (b), the light-induced self-suspended proppants in the water pass through the modified polyacrylamide on the surface of the quartz sand, and quickly absorb water and swell, and the suspension volume can reach 3 to 5 times that of the original quartz sand, slowing down the sedimentation rate of the quartz sand proppants and increasing the migration distance of the quartz sand proppants in the rock cracks, thereby increasing oil production.
[0058] Furthermore, in order to test the expansion multiple of the proppant prepared by the present invention, the specific test method is as follows: add 10 mL of anhydrous kerosene to a clean and dry 25 mL measuring cylinder, then weigh 2 g (accurate to 0.1 mg) of the dried sample and put it into the measuring cylinder, read the volume V0 increased after the sample is put in, and the volume is the dry sample volume. Weigh 2 g (accurate to 0.1 mg) of the dried sample again and put it into a 250 mL stoppered measuring cylinder, add tap water to the 200 mL mark. Place the measuring cylinder on a horizontal operating table and leave it at room temperature for 24 hours. The volume V1 of the sample after expansion is read, and the expansion multiple p´=V1 / V0. The test results are shown in Table 1. It can be seen from Table 1 that as the mass of N,N'-methylenebisacrylamide (MBA) increases, the crosslinking density of polyacrylamide is modified. When the crosslinking density is too high, the cohesion between the molecular chains of polyacrylamide is enhanced, thereby showing a lower expansion coefficient. When the monomer concentration is lower than 25%, the collision probability between each monomer and its free radical is reduced, resulting in the hindrance of the growth of the long chain. As the monomer concentration increases, the rate of chain transfer and chain termination is accelerated, and the expansion multiple gradually increases. When the monomer mass fraction is too large, the viscosity of the system has increased to a large extent. At the same time, the polymerization heat cannot be dissipated in time, resulting in a sudden rise in the system temperature, an accelerated chain initiation rate, an increase in the free radical concentration, and accelerated chain termination and chain transfer reactions, making it difficult for the polymer to be compounded on the surface of quartz sand. Under acidic conditions, acrylamide (AM) undergoes intramolecular imidization reaction, which leads to an accelerated chain transfer rate, which is not conducive to the continued occurrence of copolymerization and reduces the expansion performance. When the pH value increases, the effect of the imidization reaction decreases and the expansion performance gradually increases. However, when the pH is 7 or higher, the polymer reaction speed accelerates, and the quartz sand and modified polyacrylamide do not have time to fully combine, resulting in some quartz sand not being coated by the modified polyacrylamide. The expansion multiple first increases and then decreases with the amount of photoinitiator used. When the initiator content is less than 0.25%, as the initiator content increases, the cross-linking sites of the reaction increase accordingly, and the cross-linking density increases, so the expansion multiple of the water-swollen body increases. When the initiator concentration exceeds 0.25%, the cross-linking sites increase further, resulting in a smaller pore size in the three-dimensional network structure, so the expansion multiple no longer increases further.
[0059]
[0060] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
[0061] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing a light-triggered self-suspending proppant, characterized in that: The following steps are involved: S1: acrylamide, vinyl monomer, sulfonic acid monomer, crosslinking agent and photoinitiator are dissolved in water by stirring, and the pH value of the system is adjusted to 3-7 to prepare a modified solution; S2: adding quartz sand into the modified liquid to carry out a light-initiated reaction to obtain the suspended proppant.
2. The method for preparing a light-triggered self-suspending proppant according to claim 1, characterized in that: In step S1, the mass ratio of acrylamide, vinyl monomer, sulfonic acid monomer and cross-linking agent is (0.2-1):(0.1-0.9):(0.07-0.15):(0.005-0.025).
3. The method for preparing a light-triggered self-suspending proppant according to claim 1, characterized in that: In step S1, the amount of the photoinitiator used is 0.05% to 0.25% of the mass of the modified liquid.
4. The method for preparing a light-triggered self-suspending proppant according to claim 1, characterized in that: In step S1, sodium hydroxide, potassium hydroxide and sodium bicarbonate are used to adjust the pH value of the system.
5. The method for preparing a light-triggered self-suspending proppant according to claim 1, characterized in that: In step S2, the quartz sand is pretreated before being added to the modified liquid; the pretreatment is to place the quartz sand in a mixed solution of water and ethanol, stir and wash it, and then dry it.
6. The method for preparing a light-triggered self-suspending proppant according to claim 5, characterized in that: The ratio of the quartz sand to the mixed solution of water and ethanol is (4-12) g: (50-90) mL.
7. The method for preparing a light-triggered self-suspending proppant according to claim 5, characterized in that: During the photo-initiated reaction, the wavelength of the light source used is one of 254 nm, 312 nm and 365 nm, and the photo-initiated reaction time is 4 to 8 hours.
8. The method for preparing a light-triggered self-suspending proppant according to claim 5, characterized in that: After the light-initiated reaction, the obtained product is dried, and the dried product is ground to 40-70 meshes to obtain the suspension proppant.
9. A light-triggered self-suspending proppant, characterized in that: The self-suspending proppant is prepared by the method according to any one of claims 1 to 8; the expansion rate of the self-suspending proppant is 3.0 to 5.
0.
10. Use of the photo-triggered self-suspending proppant as claimed in claim 9 in oil and gas production.
Citation Information
Patent Citations
Preparation method for self-suspension propping agent in laboratory
CN106634939A
Self-suspending quartz sand used as fracturing propping agent
CN111187609A
Temperature-resistant and salt-resistant fracturing fluid thickening agent and preparation method thereof
CN114106239A
Multi-response controllable cross-linked degradable gel particle temporary plugging agent as well as preparation method and application thereof
CN115160500A
Imbibition oil displacement type self-suspending proppant as well as preparation method and application thereof
CN118725843A